Tirzepatide against obesity and insulin-resistance: pathophysiological aspects and clinical evidence - Corrao, Salvatore; Pollicino, Chiara; Maggio, Dalila; Torres, Alessandra; Argano, Christiano (Frontiers in Endocrinology, 2024)
Obesity is a chronic, multifactorial disease in which accumulated excess body fat has a negative impact on health. Obesity continues to rise among the general population, resulting in an epidemic that shows no significant signs of decline. It is directly involved in development of cardiometabolic diseases, ischemic coronary heart disease peripheral arterial disease, heart failure, and arterial hypertension, producing global morbidity and mortality. Mainly, abdominal obesity represents a crucial factor for cardiovascular illness and also the most frequent component of metabolic syndrome. Recent evidence showed that Tirzepatide (TZP), a new drug including both Glucagon Like Peptide 1 (GLP-1) and Glucose-dependent Insulinotropic Polypeptide (GIP) receptor agonism, is effective in subjects with type 2 diabetes (T2D), lowering body weight, fat mass and glycated hemoglobin (HbA1c) also in obese or overweight adults without T2D. This review discusses the pathophysiological mechanisms and clinical aspects of TZP in treating obesity.